SAT0456 Long-Term Outcome in Adult Patients with Juvenile Idiopathic Arthritis: Preliminary Results from a Greek Population. (23rd January 2014) - Dimopoulou, D.; Trachana, M.; Sidiropoulos, P.; Tsitsi, P.; Moihovitou, A.; Garyfallos, A.
Abstract : Background: During the last decade there is a growing evidence on the long-term outcome of patients with juvenile idiopathic arthritis (JIA). Objectives: To describe the disease characteristics, course and long-term outcome of JIA in Greece. Methods: Patients ≥ 18 years with an established JIA, a disease onset ≥5 years and no history of > 6 months care from external rheumatologists, were enrolled in this retrospective, cohort study. Clinical, laboratory and radiographic examination were performed 17.2 years post-diagnosis. Outcome was assessed by the following tools: Health Assessment Questionnaire (HAQ), Juvenile Arthritis Damage Index (JADI), the modified Sharp/van der Heijde score of radiographic damage, while the general psychological distress, by the General Health Questionnaire (GHQ-28). Disease variables relating to the onset and course of the disease were retrospectively retrieved. Results: A total of 102 (72 females) patients were enrolled. The disease age of onset (mean + SD) was 7.7±4 years, the interval from onset to last visit 17.2±6.7 years and the patients' current age 25±5.9 years. The disease type of onset was systemic arthritis in 13 (12.7%), persistent oligoarthritis in 8(7.8%), extended oligoarthritis in 22 (21.6%), polyarthritis RF negative in 19 (18.6%) polyarthritis RF positive in 11 (10, 8%), psoriatic in 9 (8.8%), enthesitis-related arthritis in 18 (17.6%) and unclassified arthritis in 2 (1.9%). Eleven patients (10.8%) had a history of uveitis. Fifteen patients (14.7%) had additional autoimmune entities. At the last follow-up visit, 53 patients (52%) still had disease activity, according to the Wallace criteria. The remaining ones were in remission on or off medication (19, 38.7% and 24, 48.9%, respectively) or had inactive disease (6, 12.2%), but did not meet the criteria for remission. The mean patients' disease activity period during the study, was 52.6% while only 37 patients (37.7%) achieved remission off medication. After a median of 17.2 years of disease, 30 patients (29.4%) had moderate to severe disability on HAQ score, 89 (87.2%) had damage in ≥ 1 joint or joint group according to JADI A and 59 (57.8%) had extra-articular damage. The mean±SD total modified Sharp score was 153.6±140. The GHQ depicted impaired psychological status in 18 patients (18.7%). Conclusions: In this cohort, about 38% of the patients achieved ≥ 1episode of remission off medication, which is in line to previous data. On the other hand, almost 30% of the study population had a significant disability and 87% had structural damage related to continuing disease activity over prolonged periods. References: Minden K (2009). Horm Res 72:20-25 Lurati A et al (2009). J Rheumatol 36:1532-5 Disclosure of Interest: None Declared